An industrial quality control study on Huggies diaper of Kimberly-Clark Philippines Inc. - Dasmarinas, John David T.; Ki, Alfredo P. Jr; Riel, Janary M. (College of Engineering, University of the Philippines Diliman, 2006)
Statistical Quality Control deals with the use of control tools and procedures for quality improvement. In this study, methods of Process Capability Analysis are now applied on an actual setting. Kimberly-Clark Philippines, Inc. is a manufacturing company that produces health and hygiene products, one of which is the Huggies diaper, the product under study. The group aims to analyze both the current and new data of Huggies diaper weight for possible cost-reduction measures that the company is now considering. After verification of all the data's normality and process control assumption, Process Capability Analysis is carried out. It has been found out that the process capability for the reduced diaper weight is greater than that of the old weight. Thus, the cost reduction method of KCPI does not jeopardize the quality of the product. Moreover, comparison of variances and test of hypotheses suggest that cost reduction measures in the extra large diaper size can be found to be unfavorable with respect to process capability.